Implementation of Decision Tree and Item Response Theory (IRT) in SIMPATIF (Sistem Penilaian Adaptif) - Devi Kurniasari, Norma; Shobikhah, Anis; Basofi Rohman, Trian; Kurniawan , Muchamad (BEST, 2025)
This study discusses how to accurately determine the level of ability of students using Computer Adaptive Testing (CAT). In the implementation of CAT, test participants are given question items according to their abilities. This shows the difference from existing testing systems such as Computer Based Testing (CBT). ADAPTIVE in this system is an automated exam system that is carried out adaptively, adjusting the difficulty level of the questions to the ability of each examinee. The questions given depend on the answer to the previous question: true or false. If the answer is correct, then the next question item has a higher level of difficulty, while if it is wrong, the difficulty level of the next question decreases. CAT in this study is also called the term SIMPATIF (Adaptive Assessment System). The difference between CAT and SIMPATIF is from the selection of question items, in the test using the SIMPATIF application, the selection of question items using the C4.5 algorithm and IRT 3 Parameter Logistics Model (3PL). The 3 parameters are the difficulty level of the question, differentiation, and deceit. In the development of this SIMPATIF. The input attributes from the decision tree have 4 attributes, namely difficulty level, differentiation, deceiver and IRT, while the target attributes are 2, namely YES and NO. The questions used are productive subjects majoring in Multimedia at SMK PGRI 2 Sidoarjo. The study was conducted with 10 students, SIMPATIF only succeeded in 67,901% for the adaptive status of the questions. Meanwhile, if correlated with CBT 76.58%.